Early maturation counteracts relative age effects in talent selection of male U16 German handball players - Thieschäfer, L.; Schorer, J.; Beppler, J.; Büsch, D. (13. DVS-Sportspiel-Symposium - "Ludo, ergo sum - Vom Kinderspiel bis zum Leistungssport", 2024)
Introduction Relative age selection biases are associated with an underrepresentation of players born at the end of the year and vice versa. The probability of selection of relative younger players might be increased by having an advanced biological maturation status (Radnor et al., 2021). Hence, it can be hypothesized that in later birth quartiles early maturing players are overrepresented to overcome potential relative age biases in talent selection processes. The aim of the study was to investigate the birth quartile distributions and its association with maturation status of male U16 players in the talent selection of German handball.